Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00240-017-0971-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nephrostomy tract infiltration of ketamine on postoperative pain and peak expiratory flow rate in patients undergoing tubeless percutaneous nephrolithotomy: a prospective randomized clinical trial

Abstract: Ketamine, as a systemic and local analgesic, has been used to reduce postoperative pain in many studies. The present study was designed to assess the analgesic efficacy of nephrostomy tract infiltration of ketamine in postoperative pain after tubeless percutaneous nephrolithotomy (PCNL). Sixty-six patients with renal stone who were candidates for PCNL were randomized to two groups with 33 patients in each group. In group K, 20 mL saline solution containing 1.5 mg/kg ketamine was infiltrated into the nephrostom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In PNL surgery, Hosseini et al investigated the effectiveness of peritubal ketamine infiltration and Imani et al also investigated the analgesic efficacy of ropivacaine infiltration and its effects on PEFR values. In these studies, it was shown that PEFR values decreased significantly in the early postoperative period after PNL, but pain management with peritubal infiltration did not affect PEFR values positively [ 4 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PNL surgery, Hosseini et al investigated the effectiveness of peritubal ketamine infiltration and Imani et al also investigated the analgesic efficacy of ropivacaine infiltration and its effects on PEFR values. In these studies, it was shown that PEFR values decreased significantly in the early postoperative period after PNL, but pain management with peritubal infiltration did not affect PEFR values positively [ 4 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain related to PCNL may cause nausea and vomiting, and aggressive management with opioids alone can result in respiratory depression [ 4 ]. Tramadol is a weak opioid used for postoperative pain relief without causing the respiratory depression seen with other opioids.…”
Section: Introductionmentioning
confidence: 99%
“…PEFR value may decrease in the early postoperative period due to pain 19 . In PNL surgery, Hosseini et al 4 investigated the effectiveness of peritubal ketamine infiltration and Imani et al 20 also investigated the analgesic efficacy of ropivacaine infiltration and its effects on PEFR values. In these studies, it was shown that PEFR values decreased significantly in the early postoperative period after PNL, but pain management with peritubal infiltration did not affect PEFR values positively 4,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Pain related to the PCNL may cause nausea and vomiting, and aggressive management with opioids alone can result in respiratory depression 4 . Tramadol is a weak opioid used for postoperative pain relief without causing the respiratory depression seen with other opioids.…”
Section: Introductionmentioning
confidence: 99%
“…There are many ways of reducing postoperative pain. These include local anesthetic infiltration into the tract 9 reducing the renal pelvic pressure during surgery, paravertebral block (T11-L1), using postoperative opioid analgesia, reducing the size of nephrostomy tube or not placing a nephrostomy tube at all. [10][11][12][13] Multiple studies have shown that tubeless PCNL is safe and feasible for select group of patients.…”
Section: Discussionmentioning
confidence: 99%